2012
DOI: 10.1098/rsif.2012.0564
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulating tumour microenvironment in chitosan–gelatin three-dimensional scaffolds: an improvedin vitrotumour model

Abstract: Owing to the reduced co-relationship between conventional flat Petri dish culture (twodimensional) and the tumour microenvironment, there has been a shift towards threedimensional culture systems that show an improved analogy to the same. In this work, an extracellular matrix (ECM)-mimicking three-dimensional scaffold based on chitosan and gelatin was fabricated and explored for its potential as a tumour model for lung cancer. It was demonstrated that the chitosan -gelatin (CG) scaffolds supported the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 51 publications
(64 reference statements)
0
35
0
1
Order By: Relevance
“…Fabrication of random and aligned scaffolds CG scaffolds were fabricated using a modification of the freezedrying technique (Arya et al, 2012). For this, low-viscosity chitosan and gelatin type B ($ 225 Bloom viscosity) from…”
mentioning
confidence: 99%
“…Fabrication of random and aligned scaffolds CG scaffolds were fabricated using a modification of the freezedrying technique (Arya et al, 2012). For this, low-viscosity chitosan and gelatin type B ($ 225 Bloom viscosity) from…”
mentioning
confidence: 99%
“…In order to provide a more appropriate simulation of the tumor microenvironment, NCI-H460 tumoroids grown on chitosan-gelatin (CG) hydrogels were used for testing the bioactivity of the composite DDS. 37 It has been reported previously that these tumoroids are similar to tumors grown in vivo in terms of factors involved in tumor growth, tumor cell -extracellular matrix interaction, tumor invasion and metastasis, and drug resistance. 37 Therefore, these tumoroids can act as a bridging gap between the conventional two-dimensional (2-D) culture and tumors grown in vivo.…”
Section: Encapsulation Efficiency and Drug Releasementioning
confidence: 81%
“…37 It has been reported previously that these tumoroids are similar to tumors grown in vivo in terms of factors involved in tumor growth, tumor cell -extracellular matrix interaction, tumor invasion and metastasis, and drug resistance. 37 Therefore, these tumoroids can act as a bridging gap between the conventional two-dimensional (2-D) culture and tumors grown in vivo. The details of this study can be found in the supplementary material.…”
Section: Encapsulation Efficiency and Drug Releasementioning
confidence: 81%
“…Scaffolds generated by this approach have been introduced to cells by way of manual seeding and found to encourage cell growth within them . Cells are found to grow in and out of the pores, but long‐term cellular growth has not been reported widely nor have any in‐depth in vivo studies been carried out.…”
Section: Methods Of Generating Scaffolds For Engineering Functional Smentioning
confidence: 99%